Goat Science 2018
DOI: 10.5772/intechopen.71853
|View full text |Cite
|
Sign up to set email alerts
|

Development of an In Vitro Goat Mammary Gland Model: Establishment, Characterization, and Applications of Primary Goat Mammary Cell Cultures

Abstract: Alternatives to animal experiments, based on in vitro methodologies, have been suggested and adopted in the last decades in order to completely substitute or to reduce animal numbers in in vivo assays. In this chapter we describe methods for establishment, maintenance, and characterization of primary goat mammary epithelial cell cultures (pgMECs) and possible applications for which the derived primary cell model can be used instead of in vivo experiments. The established cell lines were grown in vitro for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The role of whole hk bacteria in innate immune response via Toll-like receptors has been shown [ 72 ] and heat inactivation seems to induce an elevated immune response [ 73 ]. The PMECs (primary mammary epithelial cells) resemble the physiological environment of the in vivo cells more precisely and as a model, it is helpful in explaining molecular pathways associated with host–pathogen interactions [ 74 ]. In this study, we developed an in house protocol to isolate and establish the pure PMEC culture from goat milk through a non-invasive method unlike the invasive methods of isolating cells from mammary tissue, which involves surgical intervention [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of whole hk bacteria in innate immune response via Toll-like receptors has been shown [ 72 ] and heat inactivation seems to induce an elevated immune response [ 73 ]. The PMECs (primary mammary epithelial cells) resemble the physiological environment of the in vivo cells more precisely and as a model, it is helpful in explaining molecular pathways associated with host–pathogen interactions [ 74 ]. In this study, we developed an in house protocol to isolate and establish the pure PMEC culture from goat milk through a non-invasive method unlike the invasive methods of isolating cells from mammary tissue, which involves surgical intervention [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thorough characterization of early and late passage cells present distinctive epithelial-like morphology, growth and proliferative characteristics, epithelial marker CKT-18, a non-transformed lineage throughout the passages i.e. 30-chromosome number (specific for Capra hircus ) and differentiation into milk-secreting cells on lactogenic induction [ 74 , 79 83 ]. We also demonstrated that GFP could be efficiently transfected in GMECs, which can ease the physiological, and functional study of MECs through genetic manipulation in vitro [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thorough characterization of early and late passage cells present distinctive epithelial-like morphology, growth and proliferative characteristics, epithelial marker CKT-18, a non-transformed lineage throughout the passages i.e. 30-chromosome number (specific for Capra hircus ) and differentiation into milk-secreting cells on lactogenic induction (75, 76, 77, 78, 79, 70). We also demonstrated that GFP could be efficiently transfected in GMECs, which can ease the physiological, and functional study of MECs through genetic manipulation in vitro (80).…”
Section: Discussionmentioning
confidence: 99%
“…Mammary epithelial cells were isolated from goat udder gland tissue obtained from the local slaughterhouse. The protocol for isolation of GMECs was followed from Ogorevc et al 23 with slight modifications. Briefly, the entire mammary gland of a goat was obtained immediately after slaughter, dipped in 70% ethanol, followed by 2–3 washes in 1X phosphate buffered saline (1X PBS) and processed under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%